Double metal–organic frameworks derived Fe–Co–Ni phosphides nanosheets as high-performance electrocatalyst for alkaline electrochemical water splitting. (20th January 2021) - Zhang, Xiaolong; Hu, Jinsong; Cheng, Xiaofei; Nartey, Kojo Aboagye; Zhang, Lei
Highlights: 1 The mixed metal phosphide electrocatalytic material derived by double MOF-based nano-array was prepared. 2 In ternary iron-group-based metal phosphides, (Fe-Co-Ni)P can improving the catalytic activity of the mixed metal phosphide catalyst. 3 The micro-sacle structural characteristics of the catalyst greatly enhances the synergistic effect of the three metal phosphides. 4 The he catalyst delivers excellent OER and HER activity at the high current densities in the alkaline electrolyte. ABSTRACT: An efficient bi-functional electrocatalyst, FeCoNiP@C/nickel foam (NF) toward electrochemical overall-water-splitting has been developed through a facile high-temperature phosphorization strategy using corresponding metal-organic framework as starting materials. The catalyst exhibited excellent oxygen evolution reaction (η100  = 227 mV), hydrogen evolution reaction (η100  = 136 mV) and overall-water-splitting abilities (cell voltages = 1.60 V) in 1.0 M KOH to reach the current density of 100 mA/cm 2, respectively. The striking catalytic performances may be attributable to the hydrophilic and aerophobic characteristics of the multi-component chainmail electrocatalyst on NF that are easily in contact with the electrolyte to avoid the charge transfer impediment of the conventional conductive adhesive and to cause the generated bubbles to escape quickly. More importantly, the synergistic effect produced by the multi-component phosphides greatly increases the electrocatalytic performance of the sample. Graphical Abstract: Image, graphical abstract